Criminal Law Scholarship: Three Illusions - Robinson, Paul H. (2001)
The paper criticizes criminal law scholarship for helping to construct and failing to expose analytic structures that falsely claim a higher level of rationality and coherence than current criminal law theory deserves. It offers illustrations of three such illusions of rationality. First, it is common in criminal law discourse for scholars and judges to cite any of the standard litany of the purposes of punishment -- just deserts, deterrence, incapacitation of the dangerous, rehabilitation, and sometimes other purposes -- as a justification for one or another liability rule or sentencing practice. The cited purpose gives the rules an aura of rationality, but one that is, in large part, illusory. Without a principle defining the interrelation of the purposes, nearly any rule can be justified by some purpose of punishment. Thus, a decision maker can switch among distributive principles as needed to provide an apparent rationale for whichever rule the person prefers, even if that preference is not based on rational criteria. A second example is found in a central mechanism for determining an offender's blameworthiness: the use of an individualized objective standard. The widely used mechanism avoids the problems acknowledged to attend a strictly objective standard. A person's situation and capacities are central to an assessment of whether a person can be fairly blamed for a violation, and the individualized objective standard allows the decision maker to take these into account. At the same time, the mechanism avoids reversion to a completely subjective standard, which might exempt many blameworthy cases from liability. In reality, however, the mechanism only shifts the form of the problem. Codes that use the individualized objective standard fail to provide a principle by which one can determine those characteristics of an offender with which the objective standard ought to be individualized and those with which it ought not. Without a governing principle, the issue again is left to the discretion of decision makers, with no guidance as to how that discretion is to be exercised. A final illusion obscures whether the criminal justice system is, in fact, in the business of doing justice. The criminal justice system imposes punishment and encourages moral condemnation of those found guilty of crimes. But while the system cultivates its doing-justice image, it increasingly shifts to a system of essentially preventive detention, where a violator's sanction is derived more from what is needed to incapacitate him from committing future offenses than to punish him for a past offense. There are great advantages to the deception, but also serious costs and inefficiencies. The paper discusses why some illusions are more objectionable than others and what the existence of such illusions says about modern criminal law scholarship. INTRODUCTION We criminal law theorists like to think that we are moving existing criminal law theory to a higher plateau of rationality, as furthering current understanding beyond that which was given to us by our criminal law theory predecessors. But the truth is that our advances in rationality often are less than they appear; they are sometimes advances only in their appearance of rationality. This article gives illustrations of three such illusions. As will become apparent, these illustrations are of different sorts: one demonstrates the inevitable limitation of any theoretical advance; one is an example of an inevitable limitation that has been unnecessarily retained over time; and one is a case of possibly cynical deception. The focus here is upon American criminal law and its development, but there is nothing special about American criminal law or theory on this point. These illusions are likely to have some form of counterpart in the criminal law theory of most legal systems. Available for download at http://ssrn.com/abstract=18327